2010
DOI: 10.1152/ajpregu.00628.2009
|View full text |Cite
|
Sign up to set email alerts
|

Rapid EEG desynchronization and EMG activation induced by intravenous cocaine in freely moving rats: a peripheral, nondopamine neural triggering

Abstract: Many important physiological, behavioral, and psychoemotional effects of intravenous (IV) cocaine (COC) are too fast and transient compared with pharmacokinetic predictions, suggesting a possible involvement of peripheral neural mechanisms in their triggering. In the present study, we examined changes in cortical electroencephalogram (EEG) and neck electromyogram (EMG) induced in freely moving rats by IV COC administration at low, reinforcing doses (0.25-1.0 mg/kg) and compared them with those induced by an au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 54 publications
5
43
0
2
Order By: Relevance
“…NIC Consistent with our previous work (Kiyatkin and Smirnov, 2010) and early observations in cats (Yamamoto and Domino, 1975), stress-and cue-free injection of pharmacologically neutral saline made during high-magnitude, lowfrequency sleep-like activity rapidly but transiently decreased cortical and VTA EEG total powers, with phasic decreases in a and phasic increases in b and g waves (see Figure 2). Although no visual behavioral responses typically occurred following saline injection, the effect on EMG was also significant, but much weaker than that seen with NIC or somato-sensory stimuli.…”
Section: Peripheral and Central Actions Of Nicotine M Lenoir And Ea Ksupporting
confidence: 91%
See 4 more Smart Citations
“…NIC Consistent with our previous work (Kiyatkin and Smirnov, 2010) and early observations in cats (Yamamoto and Domino, 1975), stress-and cue-free injection of pharmacologically neutral saline made during high-magnitude, lowfrequency sleep-like activity rapidly but transiently decreased cortical and VTA EEG total powers, with phasic decreases in a and phasic increases in b and g waves (see Figure 2). Although no visual behavioral responses typically occurred following saline injection, the effect on EMG was also significant, but much weaker than that seen with NIC or somato-sensory stimuli.…”
Section: Peripheral and Central Actions Of Nicotine M Lenoir And Ea Ksupporting
confidence: 91%
“…Consistent with this sensory mechanism, the pattern of EEG desynchronization induced by i.v. NIC resembled that seen with sensory stimuli (Kiyatkin and Smirnov, 2010), but the changes had definite onset latencies and were much stronger and more prolonged. Consistent with a well-known inhibiting action of general anesthesia on neural responses to somatosensory stimuli, we found that the initial components of EEG response to i.v.…”
Section: Conclusion and Functional Implicationsmentioning
confidence: 57%
See 3 more Smart Citations